5‐Aminolevulinic acid‐mediated photodynamic therapy has effective antifungal activity against Sporothrix globosa in vitro. Issue 12 (12th September 2020) - Chen, Ruili; Song, Yang; Zhen, Yu; Yao, Lei; Shi, Ying; Cui, Yan; Li, Shanshan
Summary: Background: An alternative therapy for sporotrichosis is necessary to reduce the treatment time and raise clinical efficacy. The 5‐Aminolevulinic acid‐mediated photodynamic therapy (ALA‐PDT) is a promising platform with which to treat mycoses. However, despite the worldwide prevalence of Sporothrix globosa, a causative agent of sporotrichosis, the effect of ALA‐PDT on this pathogen has not been validated. Objectives: The aim of this study was to evaluate the effect of ALA‐PDT on S globosa and the protection of melanin through an in vitro study. The mechanisms involved were also investigated. Methods: To estimate the survival rate of S globosa treated with ALA‐PDT and the protection offered by melanin, the conidia and yeast cells of wild‐type S globosa (Mel+), other clinical strains, tricyclazole‐treated Mel+ and an albino mutant strain (Mel−) were incubated with and without ALA or irradiation. Reactive oxygen species generation by Mel+ conidia induced by ALA‐PDT was assayed. SEM and TEM were conducted to obverse ultrastructural changes in the conidia. A comet assay was performed to evaluate DNA damage. Results: The survival rate of S globosa conidia and yeast cells significantly decreased following incubation with 1.19M ALA and 162 J/cm 2 irradiation in vitro. Melanin was not only capable of protecting the conidia against ALA‐PDT, but also against ALA or irradiation alone. After induction by ALA‐PDT, alterations in reactive oxygen species generation, DNA damage and ultrastructural changes were observed. Conclusions: ALA‐PDT inhibits the survival of S globosa conidia in vitro and therefore has potential for the treatment of sporotrichosis.